2016 Conventiyo a la Parriya (2017)
Actúan: Daniel Cirera, Ana María Tenaglia | Cantantes: Ana TenaglIa | Músicos: Rubén Cirigliano, Angel Morales | Colaboración general: Paco Giménez | Consultado el 3 de julio de 2017 | http://www.alternativateatral.com/obra42122-conventiyo-a-la-parriya